Deep learning with Python - Chollet, François (Shelter Island, New York : Manning Publications Co., 2018)
Deep Learning with Python introduces the field of deep learning using the Python language and the powerful Keras library. Written by Keras creator and Google AI researcher François Chollet, this book builds your understanding through intuitive explanations and practical examples. You'll explore challenging concepts and practice with applications in computer vision, natural-language processing, and generative models. By the time you finish, you'll have the knowledge and hands-on skills to apply deep learning in your own projects.
Part 1: Fundamentals of deep learning. What is deep learning? --
Before we begin: the mathematical building blocks of neural networks --
Getting started with neural networks --
Fundamentals of machine learning --
Part 2: Deep learning in practice. Deep learning for computer vision --
Deep learning for text and sequences --
Advanced deep-learning best practices --
Generative deep learning.
Includes bibliographical references and index.
ARC
Trim Education
Keywords: Python (Computer program language); Machine learning; Computer science; Neural networks (Computer science); Machine learning; Neural networks (Computer science); Python (Computer program language)